KUALITAS CEO DAN MANAJEMEN LABA RIIL: APAKAH SIKLUS HIDUP PERUSAHAAN PENTING? BUKTI DARI INDONESIA - Poppy Nurmayanti (JURNAL AL-IQTISHAD, 2021)
This study aims to examine whether chief executive officer (CEO) characteristic quality affect the real earnings management from Indonesia public companies. This study used annual reports and financial statement from Indonesia Stock Exchange especially from manufacturing sectors for period 2013-2018. To capture CEO characteristics quality, the authors develops aggregate CEO characteristics as CEO characteristics quality index namely financial expertise, educational background, professional career, tenure, age, and CEO status. This study also examines how well CEO characteristics quality index could signal the presence of earnings management. The author use life cycle proxies of DeAngelo et al (2006) to capture the dynamic nature of corporate life cycle, namely retained earnings-to-total asset (RE/TA) as growth stage and mature stage. The results show that companies with high CEO quality can suppress the occurrence of real earnings management activities both for the mature stage and for the growth stage. The findings suggest that having a general assessment of the CEO’s characteristics could signal the presence of real earnings management.